Proces doskonalenia a rachunek kosztów ciągłego doskonalenia - Pewniak-Kaliska, Olga (Continuous Improvement Process and Kaizen Costing, 2007)
The article introduces continuous improvement process as a manufacturing-friendly management. It also introduces a Kaizen Costing which derives from the continuous improvement philosophy. That is why the article shows a connection between continuous improvement process and Kaizen Costing. It describes Kaizen Costing and emphasizes the main basics.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1174, s. 410-417